Assessment of Sagittal Skeletal Base Relationship of Maxilla and Mandible by Horizontal Appraisal Method-A Comparative and Reliability Study - Paoulomi Roy; Supriya Nambiar; B. Unnikrishnan; Asavari Desai; C. Suresh (Wolters Kluwer Medknow Publications, 2018)
Introduction: The evaluation of antero-posterior apical base relationship is crucial before orthodontic diagnosis and treatment planning. Aim and Objectives: The present study is aimed to compare the credibility of five cephalometric measurements in assessing the antero-posterior jaw relationship and to assess the correlation between various measurements used for antero-posterior discrepancy, including ANB, Yen angle, Beta angle, Wits appraisal, and horizontal appraisal. Materials and Methods: A total of 99 patients aged 16 years and above patients were subdivided into skeletal Classes I, II, and III groups of 33, each based upon the ANB angle derived from the pretreatment cephalogram. Results: The results showed that AH/BH and ANB had very high sensitivity and specificity to discriminate a Class II from Class I and Class III from Class I. Wits, YEN, and Beta showed lower specificity to differentiate Class II from Class I and Wits and Yen to differentiate Class III from Class I except Beta which had 100% sensitivity to differentiate Class III from Class I. Conclusion: The horizontal appraisal method enriches the current cephalometric tools available for the clinician to assess the antero-posterior jaw relationship accurately and reproducibly.